Interaction of C1q With Pentraxin 3 and IgM Revisited: Mutational Studies With Recombinant C1q Variants - Bally, Isabelle; Inforzato, Antonio; Dalonneau, Fabien; Stravalaci, Matteo; Bottazzi, Barbara; Gaboriaud, Christine; Thielens, Nicole M. (Frontiers in Immunology, 2019)
Pentraxins and complement defense collagens are soluble recognition proteins that sense pathogens and altered-self elements, and trigger immune responses including complement activation. PTX3 has been shown to interact with the globular recognition domains (gC1q) of the C1q protein of the classical complement pathway, thereby modulating complement activity. The C1q-PTX3 interaction has been characterized previously by site-specific mutagenesis using individual gC1q domains of each of the three C1q chains. The present study is aimed at revisiting this knowledge taking advantage of full-length recombinant C1q. Four mutations targeting exposed amino acid residues in the gC1q domain of each of the C1q chains (LysA200Asp-LysA201Asp, ArgB108Asp-ArgB109Glu, TyrB175Leu, and LysC170Glu) were introduced in recombinant C1q and the interaction properties of the mutants were analyzed using surface plasmon resonance. All C1q mutants retained binding to C1r and C1s proteases and mannose-binding lectin-associated serine proteases, indicating that the mutations did not affect the function of the collagen-like regions of C1q. The effect of these mutations on the interaction of C1q with PTX3 and IgM, and both the PTX3- and IgM-mediated activation of the classical complement pathway were investigated. The LysA200Asp-LysA201Asp and LysC170Glu mutants retained partial interaction with PTX3 and IgM, however they triggered efficient complement activation. In contrast, the ArgB108Asp-ArgB109Glu mutation abolished C1q binding to PTX3 and IgM, and significantly decreased complement activation. The TyrB175Leu mutant exhibited decreased PTX3- and IgM-dependent complement activation. Therefore, we provided evidence that, in the context of the full length C1q protein, a key contribution to the interaction with both PTX3 and IgM is given by the B chain Arg residues that line the side of the gC1q heterotrimer, with a minor participation of a Lys residue located at the apex of gC1q. Furthermore, we generated recombinant forms of the human PTX3 protein bearing either D or A at position 48, a polymorphic site of clinical relevance in a number of infections, and observed that both allelic variants equally recognized C1q.